Konsep Diri dan Komunikasi Interpersonal Anak TKI (Studi Konsep Diri dan Komunikasi Interpersonal Siswa SMA Karya Pembangunan Paron Ngawi Tahun Ajaran 2015/2016) - Budi Sunariyanto; Rela Mar'ati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Abstract: The concept of self is an individual's knowledge about himself and affect his relationship with others. Through the concept of human beings learn to understand yourself and others that affect the individual's ability in interpersonal relationship. Individuals perceive or assess itself will seem obvious from all his behavior, in other words the person's behavior will be in accordance with the way individuals perceive and judge for himself. This article aims to describe the concept of self and interpersonal communication at high school student Karya Pembangunan Paron, Ngawi who comes from a family of TKI, academic year 2015/2016. The subject amounts to 4 students by using qualitative research phenomenological-methods. The research found that; (a) the subject matter also shows a less passionate and excited about in terms of development and the attainment of self because it felt did not have adequate capability to achieve the ideal expectations; (b) the communication is done subject by parents who live in the House (father/mother) went well for the subject who lives the same House. For subjects who do not live the same House stated their communication less smoothly; (c) indirect communication Patterns done the subject with his parents is not effective because it felt the messages carried not optimal. In addition because of limited time, communication is done indirectly could not capture the gesture and expression of the caller so that less satisfied.Keywords: High School Students, TKI, Concepts Of Self, Interpersonal Communication